The Role of Sharia Financial Innovation and Literacy in Improving the Performance of MSME Actors - Iman Supriadi; Rahma Ulfa Maghfiroh; Rukhul Abadi; Dewi Mumpuni Yudowati (Journal of Islamic Economic and Business Research, 2023)
This study aims to analyze the role of innovation and Islamic financial literacy in improving the performance of MSME actors in the context of Islamic economics. This study also aims to evaluate the impact of innovation and Islamic financial literacy on MSME growth and contribute to the sustainable development of MSMEs. This qualitative research applied a literature approach and document analysis to collect relevant data and information. A literature review was also conducted to identify indicators of the success of Islamic financial innovation and literacy in MSMEs and appropriate evaluation methods. Other research data included previous research results and related case studies. The results of this study revealed that MSMEs that implement Islamic financial innovation and literacy tend to experience improved performance. Product and process innovation, selection of Islamic financial instruments, and financial management by Sharia principles contributed positively to increasing MSME income, productivity, and operational efficiency. This research contributes to understanding the critical role of innovation and Islamic financial literacy in improving the performance of MSME actors. The findings of this study can serve as a reference for relevant stakeholders, including MSME actors, government, and Islamic financial institutions, in developing supporting policies and programs that strengthen innovation and Islamic financial literacy in MSMEs.